Synthesis and Characterization of Some New Heteroaromatic Compounds Having Chirality Adjacent to a 1, 3, 4‐Thiadiazole Moiety and Their Antimicrobial Activities. (14th September 2017) - Gür, Mahmut; Şener, Nesrin; Kaştaş, Çiğdem A.; Özkan, Osman Emre; Muğlu, Halit; Elmaswari, Magboule A. M.
Abstract : Through a cyclization reaction of 2‐phenylbutyric acid with N‐ phenylthiosemicarbazide and POCl3, novel 1, 3, 4‐thiadiazole derivatives were synthesized. Their structures were confirmed using IR, 1 H NMR, and 13 C NMR spectroscopies and elemental analysis. The antibacterial activities of the obtained 1, 3, 4‐thiadiazole derivatives were tested against Gram‐negative bacteria ( Salmonella enteritidis, Salmonella typhimurium, Enterobacter aerogenes, Salmonella infantis, Salmonella kentucky, and Escherichia coli ) and Gram‐positive bacteria ( Staphylococcus aureus, Bacillus subtilis, and Enterococcus durans ) using a disk diffusion method. Moreover, an antifungal activity experiment was performed against Candida albicans using the disk diffusion method. It was observed that the synthesized 1, 3, 4‐thiadiazole derivatives exhibited effective antimicrobial activity against S. aureus, E. coli, and C. albicans . Based on these results, the 1, 3, 4‐thiadiazole derivatives can be considered as a source of bioactive agents for pharmacological and medicinal applications. Abstract :